pQCT-assessed relationships between diaphyseal design and cortical bone mass and density in the tibiae of healthy sedentary and trained men and women - Capozza, Ricardo Francisco (2013)
In a pQCT study of running-trained and untrained men and women we had shown that bone mass distribution along the tibia was adapted to the usage-derived stress pattern. To study the possible association between the efficiency of diaphyseal design and bone material stiffness, we extend the analysis of the same sample to correlate pQCT indicators of the distribution (CSMIs), mass (BMC), and density (vBMD) of cortical bone tissue as descriptors of “distribution/mass” (d/m) or “distribution/quality” (d/q) relationships. The d/m and d/c curves followed positive (exponential) and negative (hyperbolic-like) equations, respectively. Distribution curves of r coefficients throughout the bone were all bell-shaped, reaching a maximum towards the mid-diaphysis. The CSMIs and BMC were higher, and vBMD was lower in men than women and in runners than non-runners. The d/m relationships were described by unique curves for all groups while d/q relationships were better adjusted to separate curves for men and women. Results support that: 1. diaphyseal design reflects the relative influence of bending/torsion stress along the bones, tending to minimize bone mass; 2. there is a trade-off between cortical bone “quality” and distribution; 3. d/m and d/q relationships are related to bone mechanical environment, and 4. d/q relationships are affected by sex.